(untitled) (PROCEEDING OF INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY STUDY, 2025)
The post-truth phenomenon has changed the way society understands truth and knowledge, causing difficulties in distinguishing between facts and opinions. This study aims to explore the influence of post-truth on society’s understanding and the role of philosophy of science in providing a framework for assessing information. The method used is a qualitative approach with descriptive analysis, involving a literature review to collect relevant data. The theoretical framework includes the concept of relativism of truth and digital literacy as a tool to improve critical thinking skills. The results of the study indicate that the lack of digital literacy contributes to the spread of disinformation, while effective digital literacy education can create a smarter and more skeptical generation. By integrating digital literacy education into the curriculum, individuals can be trained to critically evaluate the information they receive, thereby building a society that is better able to face the challenges of information in the digital era.